ANALISIS PENYIMPANGAN ANGGARAN PROYEK MENGGUNAKAN PERT DAN CPM (STUDI KASUS PADA PT ARION INTAN JAYA) - Nainggolan, Putri Fortuna; Pangaribuan, Jonner (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to analyze the causes of deviations in the project budget of Rp. 103,249,432.15 and the delay of time for 2 weeks in the clean water pipe installation project in Aek Najaji Village, Padang Sidempuan Batunadua District. This research was conducted at PT Arion Intan Jaya for the period March-July 2019. The data analysis technique used was descriptive analysis technique using Planning, Evaluation and Review Technique (PERT) and Critical Path Method (CPM). The results showed that the high budget deviations and project time delays occurred due to rocky soil excavation activities, HDPE pipe installation and pipe stockpiling carried out per kilometer, from KM-1 to KM 6.5. The sequence of activities that are not suitable, causes a waste of time and variable labor costs as well as fixed costs. The total budget allocated for manpower is Rp. 456,435,000.00 for an implementation period of 150 days and the total realized labor cost is Rp. 522,745,000.00 with a project completion time of 164 days. If a review of critical activities is carried out using PERT and CPM, the project completion time changes to 96 days with a total cost of Rp. 413,760,000.00. So there is a decrease in the budget of Rp. 42,675,000.00.